2016
DOI: 10.1080/00918369.2016.1242336
|View full text |Cite
|
Sign up to set email alerts
|

Theory in Highly Cited Studies of Sexual Minority Parent Families: Variations and Implications

Abstract: This paper includes a systematic review and citation analysis of the literature regarding sexual minority parent families, particularly attending to what theories have been used, and how. We consider the importance of theoretical frameworks for future research and implications for policy, practice, and law related to sexual minority parent families. Our review targets 30 highly cited studies located through Google Scholar (as an interdisciplinary search engine) and published within a specific time frame (2005)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 90 publications
0
33
0
Order By: Relevance
“…These children and adolescents have been found to fare as well as, or sometimes better than, those raised in mother–father parent families (Gartrell and Bos, 2010). Many of these studies were grounded in family systems theory (focusing on factors that influence a child’s growth and development over time in the context of family relationships; Goldberg, 2010; Farr et al, 2017), minority stress theory (which attributes the stress of homophobic stigmatization to health disparities found among sexual minority people; Meyer, 2003), as well as social constructionism and queer theory (which emphasize that the concept of family is subject to interpretation, and view SMP families as a challenge to traditional notions of family, gender, gender relations, and sexuality; Dunne, 2000; Oswald et al, 2005; Stacey, 2006; Goldberg and Perry-Jenkins, 2007; Goldberg, 2010; Farr et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These children and adolescents have been found to fare as well as, or sometimes better than, those raised in mother–father parent families (Gartrell and Bos, 2010). Many of these studies were grounded in family systems theory (focusing on factors that influence a child’s growth and development over time in the context of family relationships; Goldberg, 2010; Farr et al, 2017), minority stress theory (which attributes the stress of homophobic stigmatization to health disparities found among sexual minority people; Meyer, 2003), as well as social constructionism and queer theory (which emphasize that the concept of family is subject to interpretation, and view SMP families as a challenge to traditional notions of family, gender, gender relations, and sexuality; Dunne, 2000; Oswald et al, 2005; Stacey, 2006; Goldberg and Perry-Jenkins, 2007; Goldberg, 2010; Farr et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that first-generation DI SMPs might express concerns about the ways that homophobic stigmatization affected their children in the past or present (Gartrell et al, 1996, 1999, 2000, 2006; Goldberg, 2010). Drawing from social constructionism and queer theory (Dunne, 2000; Oswald et al, 2005; Stacey, 2006; Goldberg and Perry-Jenkins, 2007; Goldberg, 2010; Farr et al, 2017) we predict that SMPs might be proud of the ways that their sexual and gender non-conformity influenced cultural concepts of family and parenting in positive ways. The purpose of the current study was to explore the NLLFS parents’ perspectives on the entirety of their parenting, at the time when their children were 25 years old.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, van Eeden‐Moorefield et al () found that minority stress theory was highly relevant in their review of LGBT research in general. Although Farr et al () found that minority stress theory, surprisingly, was not used in the most highly cited articles in their review of sexual minority parent families, they predicted its influence is on the rise. For example, minority stress theory is useful in terms of continued disclosure of one's sexual and gender identity in every phase of life, including care needs and family relationships in later life.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical and empirical literature on LGBTQ families in general is primarily focused on younger LGBTQ‐parent‐headed families (Goldberg & Allen, ; Reczek, ), where the intersection among aging, family, and LGBTQ is not central. Family scholars have examined the state of explicit theory use and methodology characterizing LGBTQ family research (Allen & Mendez, ; Biblarz & Savci, ; Farr, Tasker, & Goldberg, ; Fish & Russell, ; van Eeden‐Moorefield, Few‐Demo, Benson, Bible, & Lummer, ), but the focus of these important reviews has not been explicitly on concepts such as age, aging, elder, gerontology, or older adults' families. In gerontology, as well, there is a growing interest in the complexities and diversity in how sexual and gender minorities are faring in a world still marked by marginalization and discrimination, yet with greater social and legal acceptance on the horizon.…”
Section: Families Of Lgbtq Older Adults: Pioneers In Deconstructing Tmentioning
confidence: 99%
“…This lack of formalization in studying the impact of structural factors such as laws on same-sex parent families is not surprising: Research on same-sex parent families in general has been criticized as lacking explicit theoretical frameworks and integration within the broader family psychology literature (Farr et al, 2017;van Eeden-Moorefield et al, 2018), while scientific inquiry into structural determinants of sexual minority health is a recent phenomenon in itself (e.g., Hatzenbuehler, 2010Hatzenbuehler, , 2016.…”
Section: Introductionmentioning
confidence: 99%